A cognitive-behavioural interventation programme for the enhancement of self-efficacy in the children with school learning problems - Καρμπά-Σχοινά, Χρυσούλα; Ζαφειροπούλου, Μαρία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF